Identificação de metáforas nos discursos dos presidentes Lula e Bush: uma análise baseada em linguística de corpus - Mestriner, Vivian de Mello Martins (2009)
This research aims to identify and analyze linguistic and conceptual metaphors in presidential speeches of Lula and Bush. To this end, we sought theoretical support in Corpus Linguistics (CL), which deals with the collection and use of corpora, or sets of linguistic textual data carefully collected, with the purpose of searching for a language or language variety. As such, the CL is dedicated to the exploration of language by means of empirical evidence, extracted by computer (BERBER SARDINHA, 2004:03). Besides the Corpus Linguistics, this study is based on the Conceptual Metaphor Theory postulated by Lakoff and Johnson (1980) and the approach of metaphors in Cameron (2003), on the premise that both views of metaphor are complementary, considering that the conceptual metaphor is investigated through cognition and metaphor in use by means of expressions that occur in language. One of the contributions of this work is showing how metaphors in corpora can be identified with computer help. The identification of metaphor presents several challenges for Corpus Linguistics as it depends on human trial; at the same time, CL has been criticized for not making the connection between thought and language. However, contemporary theory of metaphor have shown the relationship between the systematic use of verifiable language corpora and cognition (LAKOFF & JOHNSON, 1980). As material for analysis were selected speeches of Presidents Bush and Lula, the first due to his recent political leadership of the largest global economic power, and the second for having been leader of a country on the run to development Brazil. Although the two presidents defend quite different policy options, they share some similarities as both have had difficulties to take the second term: Lula with the fame of corruption in his government, Bush with the Iraq war. Written and spoken on-line statements and speeches have been gathered covering the first five-year mandate of both presidents, totaling 868 speeches by Lula and 819 by Bush. The program Metaphor Identifier with free availability at CEPRIL (LESS) was used to search for words with metaphorical probability. Next, the correlation of these candidates was raised through the Concord program (WordSmith Tools, version 3.0) to attest possible methaphorical use. Finally, upon identification of the linguistic and conceptual metaphors, speeches of the two presidents were contrasted seeking to understand how metaphors shape such speeches